SISTEM TUJUAN KONSUMEN PADA TAWARAN BERHUTANG - Manara, Muh. Untung (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2011)
Debt and no debt behavior is the instrument to pursuit goals. Almost all of behavior is goal-directed including debt and no debt behavior. The objective of this research was to find goals of debt and no debt behavior and to know hierarchical structure of these goals that organized on goal system.Â  Laddering technique was used to explore goals of consumer that receive and refuse debt. This technique used to find consumers goals that organized hierarchically that consist of action goal, focal goal, and super-ordinate goal. Open-ended questionnaire was developed based on laddering technique questions. Demography form was added to explore demography data. One hundred four respondents participated in this research. Participants are teachers and staffs in elementary and middle school. Content analysis was applied to all responds to analyze and categorize laddering data. From 104 respondents, there are 50 respondents receiving debt and 54 refusing debt. Total goals of consumers that receive debt are 720 and 383 for respondents that refuse debt. Result of content analysis show that action goals of consumers receiving debt are to invest, for housing, for children, for education, for appliance, secondary need, and to save. On the focal goals level, the most goals mentioned were economic established, self quality, children competency, having quality home, family harmony, improve life, prepared motive, and social motive. On the highest level, super-ordinate goals of consumer receive debt were dominated by productivity and efficiency, followed by happiness and spirituality. While for consumer refusing debt, action goal was refuse debt. On the Focal goal level, the frequently goal mentioned were being free of debt, hassle free, prudence, repay debt first, and just enough. Finally, super-ordinate goals of consumer refuse debt were dominated by comfortable life followed by happiness and spirituality. There were three demography variable that can be differentiated the choice receiving debt or refusing debt namely: age, job status, and ever or never taking debt on ten last years.Â